Single-Cell TCR Sequencing Uncovers Remodeling of the Immune Repertoire After a Short-Term Gluten-Free Diet in Pediatric Celiac Disease. - Martin‐Masot, Rafael; Herrador-López, Marta; Navas-López, Víctor Manuel; Carmona, Francisco David; González-Muñoz, Sara; López-Isac, Elena; Nestares, Teresa; Bossini-Castillo, Lara (MDPI, 2025)
Celiac disease (CD) is a chronic autoimmune disorder triggered by gluten in genetically susceptible individuals. While gluten-free diet (GFD) remains the primary treatment, the molecular mechanisms underlying immune reconstitution remain poorly understood in pediatric populations. This study aimed to characterize T cell receptor (TCR) repertoire remodeling in pediatric CD patients following short-term GFD. We conducted a longitudinal observational study analyzing peripheral blood circulating T cells from five pediatric CD patients at two time points: pre-GFD (at diagnosis) and post-GFD (after 9–10 months of strict dietary adherence). Single-cell TCR sequencing was performed to analyze clonotype diversity, gene usage patterns and TRAV-TRBV pairing combinations. Analysis of 9661 T cells revealed significant TCR repertoire remodeling post-GFD. Expanded clones, predominantly cytotoxic CD8+ T cells, contracted post-GFD (p = 0.02), while increasing clonotype diversity. Notably, specific αβ chain pairings underwent clear reorganization in the complete T cell compartment. Pathogenic combinations were depleted post-GFD, especially in CD4+ T cells, while beneficial pairings became enriched. GFD induced comprehensive TCR repertoire remodeling, revealing that changes occur at the level of specific TCR pairings rather than individual gene usage. Our findings highlight the precision of single-cell approaches in capturing functionally relevant immune changes for monitoring treatment response in pediatric CD.
Keywords: Enfermedad celíaca en niños; Dietas sin gluten; Genes codificadores de los receptores de linfocitos T; Celiac disease; TCR; T-cell; Pediatric; Gluten-free diet